Validity of the ActiGraph GT3X+ and BodyMedia SenseWear Armband to estimate energy expenditure during physical activity and sport. Issue 3 (March 2018) - Gastin, Paul B.; Cayzer, Cassy; Dwyer, Dan; Robertson, Sam
Abstract: Objectives: The purpose of this study was to assess the validity of the ActiGraph GT3X+ (GT3X+) and the BodyMedia SenseWear Armband (SWA) to estimate energy expenditure (EE) during physical activity and field sport movements. Design: Criterion validity. Methods: Twenty-six active adults completed a single 90 min session involving alternating intervals of exercise (5 min) and recovery (10 min). Exercise involved walking (4 km/h), jogging (8 km/h), running (12 km/h) or a sport-simulated circuit (three intervals). Participants wore two triaxial accelerometers (GT3X+ and SWA) and a portable gas analyser (MetaMax 3B), used as the criterion measure. Results: Total EE was significantly underestimated (p < 0.01) by the GT3X+ (mean bias ± SD: −374.5 ± 132.84 kJ; % difference = −29.3%) and SWA (−244.3 ± 148.0 kJ; −18.2%). Overestimations were made by both accelerometers during the walk (GT3X+: 27.4 ± 30.8 kJ; SWA: 32.1 ± 15.4 kJ) and jog (38.0 ± 30.0 kJ; 34.5 ± 31.6 kJ). Underestimations were evident during the run (−41.2 ± 25.1 kJ; −43.8 ± 33.5 kJ) and circuit (C1: GTX+: −127.2 ± 41.6 kJ; SWA: −86.1 ± 40.2 kJ). Error of estimation increased in magnitude as the intensity of exercise increased (GT3X+: 40.8–143.0 kJ; SWA: 35.5–102.0 kJ). Conclusions: The ActiGraph GT3X+ and BodyMedia SWA do not provide valid EE estimates across a range of exercise modalities and intensities when compared to a criterion measure. Poor accuracy and large precision errors, particularly during high intensity and intermittent movement patterns, suggest these devices have limitations and should be used cautiously in the field.